Peran Komunikasi Efektif Dalam Meningkatkan Produktivitas dan Kolaborasi di Lingkungan Perkantoran SD Swasta Islam Salsabila Medan - Rambe, Nazila Fujianti; Harahap, Hasti Ananda; Nurfadillah, Agum; Hutagalung, Rahmad Rizki; Darmansah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Effective communication is a crucial element in the success of school clerical management. This study aims to analyze the role of effective communication in enhancing productivity and collaboration in the office environment of SDS ISLAM SALSABILA Medan. The research method used was qualitative descriptive with interview, observation, and documentation techniques. The results of the study showed that open, structured, and participatory communication contributed significantly to increased staff work productivity as well as collaboration across departments in the school office. The article concludes that effective communication is a key foundation in building quality school administrative governance.